Tribe, ecology, and development - Pattnaik, Renuka (New Delhi : Rajat Publications, 2000)
Study with reference to Katkari, Kolam, and Madia Gond tribes in Maharashtra, India.
Includes bibliographical references (p. [187]-204) and index.
Keywords: Tribes -- India; India -- Sheduled tribes; India -- Social life and customs; India -- social policy